Genetic conservation within subtypes in the hepatitis B virus pre-S2 region - Kidd-Ljunggren, Karin; Couroucé, Anne-Marie; Öberg, Monica; Kidd, Alistair H. (Journal of General Virology, 1994)
The antigenic determinants for the main hepatitis B vims (HBV) subtypes adw, adr, ayw and ayr lie in the S (surface) polypeptide. Two amino acid residues in particular, encoded by the S gene at codon positions 122 and 160, have been postulated to determine the different antigenic subtypes. In contrast, the 165 nucleotide pre- S2 gene encodes an immunodominant region common to all subtypes that can give rise to neutralizing antibodies. We have characterized the pre-S2 gene sequences of 29 HBV strains of the three main subtypes, adw, ayw and adr. Seven base positions showed variation that was entirely subtype-specific, with six of these variations leading to subtype-specific amino acid differences. This finding affords the possibility of using pre-S2 sequences for genetic subtyping. Two ayw strains from unrelated patients infected in the Middle East had identical pre-S2 sequences with a block of 12 nucleotides deleted. A geographical correlation with subtype observed from serological results was also apparent from phylogenetic analysis of DNA identities within the pre- S2 region. The results support the concept that the main HBV subtypes truly represent families of phylogen- etically different strains.